On the distribution of Gonyosoma prasinum (Blyth, 1854) and Gonyosoma coeruleum Liu, Hou, Ye Htet Lwin, Wang & Rao, 2021, with a note on the status of Gonyosoma gramineum Günther, 1864 (Squamata: Serpentes: Colubridae) - David, Patrick; Campbell, Patrick D.; Deuti, Kaushik; Hauser, Sjon; Luu, Vinh Quang; Nguyen, Truong Quang; Orlov, Nikolai; Pauwels, Olivier S. G.; Scheinberg, Lauren; Sethy, Priyadarsi Girija Sankar; Smits, Ton; Teynié, Alexandre; et al. (Zootaxa, 2022)
Based on 85 examined specimens, photographs of living specimens and illustrations published in the literature, we refine the distribution ranges of both Gonyosoma prasinum (Blyth, 1854) and of the recently described species Gonyosoma coeruleum Liu, Hou, Ye Htet Lwin, Wang & Rao, 2021, which was not clearly addressed in its original description. We also redescribe the syntypes of Coluber prasinus Blyth, 1854 and the holotype of Gonyosoma gramineum Günther, 1864, we discuss the status of this latter taxon, and we describe the hemipenial morphology of G. coeruleum.